Factors Associated with Reported Infection and Lymphedema Symptoms among Individuals with Extremity Lymphedema. Issue 5 (September 2015) - Deng, Jie; Fu, Mei R.; Armer, Jane M.; Cormier, Janice N.; Radina, Elise M.; Thiadens, Saskia R.J.; Weiss, Jan; Tuppo, Catherine M.; Dietrich, Mary S.; Ridner, Sheila H.
Abstract : Purpose: : This study aimed to examine factors associated with reported infection and symptoms among individuals with extremity lymphedema. Design: : A cross‐sectional study was used. Methods: : Data were collected from a survey supported by the National Lymphedema Network from March 2006 through January 2010. A total of 1837 participants reported having extremity lymphedema. Logistic regression analyses were used. Findings: : Factors associated with reported infection among individuals with extremity lymphedema included male gender, decreased annual household income, decreased self‐care, self‐report of heaviness, and lower extremity as opposed to upper extremity. Factors associated with symptoms included infection, decreased self‐care, lower knowledge level of self‐care, decreased annual household income, and presence of secondary lower extremity lymphedema. Conclusions/Clinical Relevance: : Select factors of income, self‐care status, and site of lymphedema were associated with increased occurrence of infection and symptoms among individuals with extremity lymphedema. Longitudinal studies are needed to identify risk factors contributing to infections and symptoms in individuals with lymphedema.